Comparison of Touhy and Quincke needles on intravascular injection rate in lumbar transforaminal epidural block: a randomized prospective trial. Issue 8 (26th May 2021) - Soh, Hyojung; Jeong, Yujin; Kim, Eung Don
Abstract : Background: Transforaminal epidural steroid injection is widely used in clinical practice to effectively deliver injectate into the ventral epidural space. Complications associated with intravascular injection such as spinal cord infarction and paraplegia can occur during transforaminal epidural steroid injection. To improve the safety of the procedure, avoidance of intravascular injection is crucial, for which appropriate needle selection is important. The primary aim of this study was to compare intravascular injection rates during transforaminal epidural steroid injection between commonly used Quincke and Tuohy needles. Method: Two hundred and four transforaminal epidural steroid injection cases were randomly assigned to one of two needle groups (22-gage Quincke needle or 22-gage Tuohy needle). Intravascular injection was evaluated using digital subtraction angiography. Spread of contrast medium to the ventral and medial epidural spaces was evaluated. Procedure time was compared between the two needle types. Results: The overall incidence of intravascular injection was 7.8%. The rate of intravascular injection was significantly lower in the Tuohy needle group than the Quincke needle group (2.9% vs 12.7%, p=0.009). The ventral and medial epidural spread rates of the Tuohy needle group were 92.2% and 95.1%, respectively, significantly higher than those of the Quincke needle group. The procedure time was shorter in the Tuohy needle group than in the Quincke needle group (97.4 (19.3) seconds vs 117.8 (31.9) s; mean difference −20.40 (95% CI −34.35 to −6.45), p=0.005). Conclusions: In conclusion, Tuohy needles had a lower intravascular injection rate and higher medial and ventral epidural spreading rates than Quincke needles. Trial registration number: KCT0002095.